Manufacturing method of carbon-based nonwoven fabric for cesium adsorption and cesium adsorbent

JP7641760B2Active Publication Date: 2025-03-07井上 浩义
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021027406
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-24
Publication Date
2025-03-07
Estimated Expiration
2041-02-24

AI Technical Summary

Benefits of technology

【0021】 本発明のセシウム吸着用の炭素系不織布の製造方法によれば、原子炉あるいは環境中などから放射性セシウムを回収することができ、廃棄処理する際にもその処理が簡便なセシウム吸着用の炭素系不織布(セシウム吸着材)を製造することができるという効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641760000005
    Figure 0007641760000005
  • Figure 0007641760000006
    Figure 0007641760000006
  • Figure 0007641760000007
    Figure 0007641760000007
Patent Text Reader

Abstract

To provide a method for producing a carbon-based nonwoven fabric for cesium adsorption having cesium adsorptivity, and a cesium adsorbent.SOLUTION: A method for producing a carbon-based nonwoven fabric for cesium adsorption includes immersing a carbon fiber-made nonwoven fabric in a surfactant solution containing a surfactant and then drying the resultant material, to produce the carbon-based nonwoven fabric for cesium adsorption.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a carbon-based nonwoven fabric for cesium adsorption and a cesium adsorbent. More specifically, the present invention relates to a method for producing a carbon-based nonwoven fabric for cesium adsorption having cesium adsorption performance and a cesium adsorbent. [Background technology]

[0002] The accident at the Fukushima Daiichi Nuclear Power Plant of Tokyo Electric Power Company in 2011 released a large amount of radioactive material into the environment. Among the radioactive materials released, cesium-134 (Cs-134) and cesium-137 (Cs-137), which are the products of nuclear reactions of uranium, were released in large quantities and have long half-lives of 2.1 years and 30 years, respectively. In addition, these cesium species have a high tendency to bind to soil, so they remain in the environment for a long time.

[0003] Furthermore, since this cesium behaves in a similar manner to potassium, which is essential for living organisms, and is expected to have an impact on the ecosystem, it is necessary to remove it from the environment.

[0004] A method of removing cesium that uses zeolite as an inorganic ion exchanger has been known. Specifically, there are known methods of mixing zeolite with water containing cesium (target of cesium removal; cesium ions) and then obtaining a precipitate containing cesium, and methods of passing water through a cylinder filled with zeolite. Note that the contaminated water treatment device "SARRY" (manufactured by Toshiba Energy Systems & Solutions Corporation) used at the Tokyo Electric Power Company's Fukushima Daiichi Nuclear Power Plant employs a method of passing water through a cylinder filled with zeolite.

[0005] Other methods than those using zeolite include those described in Patent Documents 1 and 2, which specifically include a method using a PVA membrane carrying a cation exchange resin or an adsorbent, a method using a cation exchange membrane with an exchange group introduced, etc. Furthermore, a method using Prussian blue, a dye that specifically adsorbs to cesium ions, either directly or after being adsorbed on fibers, etc., is also being explored. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2014-108379 A [Patent Document 2] International Publication No. 2014 / 010417 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the removal method using zeolite, it takes time and effort to precipitate the cesium-containing zeolite (obtain a precipitate), and to dehydrate and remove the precipitate. Furthermore, used zeolite has a large volume, which tends to cause problems such as the need to secure space for waste management and the associated costs, and there is room for improvement.

[0008] In addition, methods using polyvinyl alcohol (PVA) membranes or cation exchange membranes tend to release harmful substances when incinerated, and there is still room for improvement in terms of ease of disposal. The method using Prussian blue has issues such as the difficulty of separating the substance (cesium-Prussian blue bound substance) from the free substance (cesium ion and Prussian blue) after adsorption.

[0009] The present invention has been made in view of such conventional technology, and an object of the present invention is to provide a method for producing a carbon-based nonwoven fabric for adsorbing cesium, which is capable of recovering radioactive cesium from the environment and is easy to dispose of when disposed of, and a cesium adsorbent. [Means for solving the problem]

[0010] According to the present invention, there is provided a method for producing a carbon-based nonwoven fabric for adsorbing cesium, and a cesium adsorbent, as shown below.

[0011] [1] A method for manufacturing a carbon-based nonwoven fabric for cesium adsorption, comprising immersing a carbon fiber nonwoven fabric in a surfactant solution containing a surfactant and then drying the fabric.

[0012] [2] The method for producing a carbon-based nonwoven fabric for cesium adsorption described in [1] above, wherein the surfactant contained in the surfactant solution is polyoxyalkylene lauryl ether.

[0013] [3] The method for producing a carbon-based nonwoven fabric for adsorbing cesium according to [1] or [2] above, wherein the concentration of the surfactant contained in the surfactant solution is 0.05 to 5 mass %.

[0014] [4] A method for producing a carbon-based nonwoven fabric for adsorbing cesium according to any one of [1] to [3] above, wherein the nonwoven fabric is made of carbon fibers that have been treated to be water-repellent with a first water-repellent resin.

[0015] [5] A method for producing a carbon-based nonwoven fabric for cesium adsorption described in [4] above, in which the nonwoven fabric is made by coating the carbon fiber with a coating agent containing a second water-repellent resin and a conductive material after the carbon fiber has been treated to be water-repellent with the first water-repellent resin.

[0016] [6] The first water-repellent resin and the second water-repellent resin are each a fluororesin, The method for producing a carbon-based nonwoven fabric for cesium adsorption according to [5] above, wherein the conductive material is carbon black.

[0017] [7] A method for producing a carbon-based nonwoven fabric for cesium adsorption, comprising: preparing a nonwoven fabric made of carbon fiber; and subjecting the carbon fibers of the nonwoven fabric to a water-repellent treatment using a first water-repellent resin to obtain a carbon-based nonwoven fabric for cesium adsorption.

[0018] [8] A method for producing a carbon-based nonwoven fabric for adsorbing cesium described in [7] above, in which the nonwoven fabric is one which has been subjected to the water-repellent treatment and then coated with a coating agent containing a second water-repellent resin and a conductive material.

[0019] [9] A nonwoven carbon fiber fabric; A cesium adsorbent comprising: a surfactant attached to the surface of the nonwoven fabric.

[0020]

[10] The cesium adsorbent described in [9], wherein the surfactant is polyoxyalkylene lauryl ether. Effect of the Invention

[0021] According to the method for producing a carbon-based nonwoven fabric for adsorbing cesium of the present invention, it is possible to recover radioactive cesium from a nuclear reactor or the environment, and it is possible to produce a carbon-based nonwoven fabric for adsorbing cesium (cesium adsorbent) that is easy to dispose of.

[0022] The cesium adsorbent of the present invention is capable of recovering radioactive cesium from a nuclear reactor or the environment, and has the effect of simplifying disposal thereof. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is an explanatory diagram showing a schematic diagram of an apparatus used for electrochemical measurement in which a carbon-based nonwoven fabric manufactured by the method for manufacturing a carbon-based nonwoven fabric for cesium adsorption of the present invention is arranged. [Diagram 2]FIG. 2 is a light-and-shade explanatory diagram that illustrates a carbon-based nonwoven fabric in the device shown in FIG. 1 and solution phases of different concentrations partitioned by this carbon-based nonwoven fabric. [Diagram 3] 1 is a graph showing the measurement results of the effect of the coexistence of inorganic ions on the critical micelle concentration of a surfactant (polyoxyalkylene lauryl ether) used in the manufacturing method of the carbon-based nonwoven fabric for cesium adsorption of the present invention. [Figure 4] 1 is a chart showing the results of mass spectrometry (Time-Of-Flight mass spectrometry; TOF-MS) of each carbon-based nonwoven fabric. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The following describes the embodiments of the present invention, but the present invention is not limited to the following embodiments. In other words, it should be understood that the scope of the present invention includes any modifications and improvements to the following embodiments based on the ordinary knowledge of a person skilled in the art without departing from the spirit of the present invention.

[0025] (1) Manufacturing method of carbon-based nonwoven fabric for cesium adsorption (first embodiment): One embodiment of the method for producing a carbon-based nonwoven fabric for cesium adsorption of the present invention is a production method in which a nonwoven fabric made of carbon fibers is immersed in a surfactant solution containing a surfactant, and then dried to obtain a carbon-based nonwoven fabric for cesium adsorption (cesium adsorbent).

[0026] According to the method of the present invention for producing a carbon-based nonwoven fabric for adsorbing cesium, it is possible to produce a carbon-based nonwoven fabric for adsorbing cesium that can recover radioactive cesium from the environment and that is easy to dispose of when disposed of (specifically, it does not require burial, and when incinerated, there is no release of harmful substances such as dioxins, making it easy to dispose of).

[0027] (1-1) Carbon fiber nonwoven fabric: The carbon fiber nonwoven fabric used in the present invention is a web or sheet composed of only carbon fibers, or carbon fibers that have been subjected to a water-repellent treatment or a coating treatment after the water-repellent treatment. In such a nonwoven fabric, the carbon fibers (i.e., filaments that are a plurality of single fibers) are gathered together to form a strand that is a bundle. Therefore, the nonwoven fabric has a three-dimensional net shape, and a plurality of pores are formed. Because of this structure, the nonwoven fabric can be used as a filter for removing desired fine particles, etc.

[0028] The length of the carbon fibers is not particularly limited, but may be, for example, about 30 to 100 mm. The length of the carbon fibers is defined as the average length of 100 carbon fibers randomly selected from a nonwoven fabric made of carbon fibers.

[0029] The thickness of the carbon fibers is not particularly limited, but may be, for example, about 5 to 30 μm. The thickness of the carbon fibers is the average value of 100 carbon fibers randomly selected from a nonwoven fabric made of carbon fibers, and is the average value of the thickness of a single fiber (filament) (if the thickness of a single fiber is not constant, the thickness of the thinnest part).

[0030] The thickness of the nonwoven fabric is not particularly limited and can be set according to the application. For example, it is preferably about 100 to 500 μm. When two or more sheets of carbon fiber nonwoven fabric are laminated, the thickness refers to the thickness of the laminate in which two or more sheets of carbon fiber nonwoven fabric are laminated. In other words, it is preferable that the thickness of the entire nonwoven fabric, which is the filter, falls within the above range.

[0031] The basis weight of the nonwoven fabric is not particularly limited, and is, for example, 40 to 400 g / m 2 It can be about that.

[0032] The average pore size of the nonwoven fabric is preferably about 0.01 to 500 μm, more preferably about 0.02 to 300 μm, and even more preferably about 0.03 to 100 μm. When the average pore size is within the above range, a nonwoven fabric having better cesium adsorption ability can be obtained. The average pore size of the nonwoven fabric is a value measured by mercury intrusion porosimetry.

[0033] The nonwoven fabric may be carbon fiber treated with a first water-repellent resin to make it water-repellent. By using a nonwoven fabric made of carbon fiber treated in this way to make it water-repellent, it is possible to produce a carbon-based nonwoven fabric with improved cesium adsorption ability.

[0034] The first water-repellent resin may be a fluororesin, etc. Use of a fluororesin can provide chemical stability to the entire membrane and can improve the cesium adsorption ability.

[0035] The nonwoven fabric may be one in which carbon fibers are treated with a first water-repellent resin to make them water-repellent, and then coated with a coating agent containing a second water-repellent resin and a conductive material (MPL (microporous layer) coating). By adopting such a coating process, a microporous layer is formed on the surface of the nonwoven fabric by the coating process, and therefore a carbon-based nonwoven fabric with even better cesium adsorption ability can be produced.

[0036] The second water-repellent resin may be a fluororesin. By using a fluororesin, a carbon-based nonwoven fabric for cesium adsorption with better performance can be manufactured. The second water-repellent resin may be the same as the first water-repellent resin.

[0037] Examples of fluororesins include polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkylvinyl ether copolymer (PFA), etc. Among these, polytetrafluoroethylene (PTFE) is preferred.

[0038] Further, examples of the conductive material include carbon black such as furnace black, acetylene black, lamp black, and thermal black, as well as flake graphite, flaky graphite, earthy graphite, artificial graphite, expanded graphite, and flake graphite. Among these, it is preferable to use carbon black because it has pores.

[0039] The carbon fiber nonwoven fabric used in the present invention may be a single sheet or a laminate of two or more sheets.

[0040] (1-2a) Preparation of carbon fiber nonwoven fabric: The carbon fiber nonwoven fabric can be produced by a conventionally known method, for example, as follows: That is, the carbon fiber nonwoven fabric can be produced by a method having a step A of producing a carbon fiber precursor fiber nonwoven fabric using carbon fiber precursor fibers, and a step B of carbonizing the carbon fiber precursor fiber nonwoven fabric produced in the step A.

[0041] Here, the carbon fiber precursor fiber is a fiber that is converted into carbon fiber by carbonization. Such fibers are not particularly limited, but examples thereof include polyacrylonitrile (PAN)-based fibers, pitch-based fibers, lignin-based fibers, polyacetylene-based fibers, polyethylene-based fibers, polyvinyl alcohol-based fibers, cellulose-based fibers, and polybenzoxazole-based fibers. The carbon fiber precursor fiber may be of one type alone or two or more types.

[0042] In the above-mentioned step A, a web is formed using carbon fiber precursor fibers, and the web is bonded into a cloth-like shape by entangling, heat fusion, binder adhesion, or the like, thereby producing a carbon fiber precursor fiber nonwoven fabric.

[0043] In the above-mentioned step B, the carbon fiber precursor fiber nonwoven fabric produced in step A is carbonized. The carbonization conditions are not particularly limited, and a method known in the field of carbon fiber materials can be appropriately adopted. For example, the carbonization is a process in which the carbon fiber precursor fiber is baked in an inert gas atmosphere. More specifically, the carbon fiber precursor fiber can be heated to, for example, 800°C or higher under an inert gas atmosphere while supplying an inert gas such as nitrogen or argon.

[0044] When performing water-repellent treatment, after the above-mentioned step B, the carbonized carbon fiber precursor fiber nonwoven fabric may be coated with a first water-repellent resin (that is, a water-repellent agent) and then heat-treated.

[0045] Furthermore, when forming a microporous layer on the surface of carbon fiber by coating treatment, a coating agent containing a second water-repellent resin and a conductive material is applied to a carbon fiber precursor fiber nonwoven fabric that has been subjected to a water-repellent treatment to form a coating film, and then the coating film can be dried at a temperature of, for example, 80 to 150° C., and then heat-treated. The coating agent can be applied by a known method such as screen printing, slot die coating, doctor blade coating, etc.

[0046] (1-2) Surfactant solution: The surfactant solution used in the present invention (first embodiment) contains a surfactant. By using such a surfactant solution, a nonwoven fabric (filter) with good cesium adsorption capacity can be manufactured. That is, a carbon-based nonwoven fabric for cesium adsorption can be manufactured. In the present invention (first embodiment), a surfactant is used in the manufacturing process and the method of attaching the surfactant to the surface of the carbon fiber nonwoven fabric can be adopted to obtain a nonwoven fabric with improved cesium adsorption capacity.

[0047] Examples of the surfactant contained in the surfactant solution include polyoxyalkylene lauryl ether, sorbitan tristearate, and n-octanoyl-N-methyl-D-glucamine (MEGA-8). Among these, polyoxyalkylene lauryl ether is preferable. When polyoxyalkylene lauryl ether is used, a nonwoven fabric having improved cesium adsorption capacity can be obtained more reliably.

[0048] The surfactant solution may contain one type of surfactant, or may contain two or more types of surfactants.

[0049] The concentration of the surfactant contained in the surfactant solution is not particularly limited, but is preferably 0.05 to 10% by mass, and particularly preferably 0.1 to 2% by mass. When the surfactant concentration is within the above range, a nonwoven fabric with improved cesium adsorption capacity can be obtained. If the concentration is below the above lower limit, there is a tendency that sufficient improvement in cesium adsorption capacity cannot be obtained. If the concentration is above the above upper limit, there is a limit to the amount of surfactant adsorbed by the nonwoven fabric (filter), and the amount of adsorption tends not to increase sufficiently.

[0050] (1-3) Immersion: The time for immersing the nonwoven fabric in the surfactant solution is not particularly limited, but may be, for example, 1 to 10 minutes.

[0051] (1-4) Drying: The drying conditions for the nonwoven fabric after immersion in the surfactant solution are not particularly limited, but may be, for example, at 50 to 80° C. for 0.5 to 2 hours.

[0052] (2) Manufacturing method of carbon-based nonwoven fabric for cesium adsorption (second embodiment): A second embodiment of the method for manufacturing a carbon-based nonwoven fabric for cesium adsorption is a manufacturing method in which a nonwoven fabric made of carbon fiber is prepared, and the carbon fibers of this nonwoven fabric are treated to make them water-repellent with a first water-repellent resin, thereby obtaining a carbon-based nonwoven fabric for cesium adsorption.

[0053] As the carbon fiber nonwoven fabric, the same carbon fiber nonwoven fabric as that shown in the above-mentioned first embodiment can be used.

[0054] As the first water-repellent resin, a resin similar to the first water-repellent resin and the second water-repellent resin in the first embodiment described above can be used, and the nonwoven fabric can be further subjected to both a water-repellent treatment and a coating treatment, as in the first embodiment described above.

[0055] (3) Cesium adsorbent (first embodiment): The cesium adsorbent of the present invention comprises a nonwoven fabric made of carbon fibers and a surfactant attached to the surface of the nonwoven fabric.

[0056] Such a cesium adsorbent can recover radioactive cesium from the environment. In addition, it is easy to dispose of it when it is disposed of. That is, the carbon-based nonwoven fabric of the present invention can prevent the generation of SOx, NOx, dioxins, etc. during incineration, so it can be easily disposed of after use.

[0057] (3-1) Carbon fiber nonwoven fabric: The carbon fiber nonwoven fabric may be appropriately made of the same carbon fiber nonwoven fabric as that explained in the above-mentioned method for producing a carbon-based nonwoven fabric for cesium adsorption of the present invention.

[0058] Here, the carbon fiber nonwoven fabric may be composed of only carbon fibers, or may be composed of carbon fibers that have been subjected to a water-repellent treatment using a water-repellent resin, or may be composed of carbon fibers that have been further coated after the water-repellent treatment. That is, the carbon fiber nonwoven fabric may be (a) a nonwoven fabric made of carbon fibers, or (b) a nonwoven fabric made of carbon fibers whose surfaces have been treated for water repellency (i.e., a nonwoven fabric made of carbon fibers (water-repellent carbon fibers) whose surfaces have been treated for water repellency), or (c) a nonwoven fabric made of carbon fibers whose surfaces have been treated for water repellency and further having a microporous layer on the water-repellent surface (i.e., a nonwoven fabric made of water-repellent carbon fibers).

[0059] (3-2) Surfactant: The surfactant may be the same as that explained in the above-mentioned method for producing a carbon-based nonwoven fabric for cesium adsorption of the present invention.

[0060] As described above, examples of the surfactant include polyoxyalkylene lauryl ether, sorbitan tristearate, and n-octanoyl-N-methyl-D-glucamine (MEGA-8). Among these, polyoxyalkylene lauryl ether is preferable. When polyoxyalkylene lauryl ether is used, a nonwoven fabric having improved cesium adsorption capacity can be obtained more reliably.

[0061] (3-3)Physical properties: The cesium adsorbent of the present invention has an air permeability of 50 to 800 L / (m 2 ·sec), and 100 to 500 L / (m 2 sec), more preferably. Alternatively, the Gurley seconds (ISO5636-5) is preferably 1 to 100 sec, and more preferably 5 to 80 sec. When the air permeability is within the above range, a good balance between the filtration time and the filtration efficiency is achieved. The air permeability is a value measured according to DIE EN ISO 9237.

[0062] (4) Cesium adsorbent (second embodiment): The cesium adsorbent of the present invention (second embodiment) may have a carbon fiber nonwoven fabric on the surface of which a water-repellent resin is arranged. That is, it may be manufactured by the second embodiment of the manufacturing method of the carbon-based nonwoven fabric for cesium adsorption described above. This cesium adsorbent is an embodiment that does not have a surfactant.

[0063] The water-repellent resin may be the same as the water-repellent resin described above.

[0064] (5) Method for using the cesium adsorbent of the present invention: The cesium adsorbent of the present invention can be used as a filter for removing cesium. More specifically, it can be used as a decontamination filter for removing radioactive cesium from contaminated water generated at the Tokyo Electric Power Company's Fukushima Daiichi Nuclear Power Plant, and from soil, water areas, agricultural products, and other contaminated materials due to environmental release. EXAMPLES

[0065] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0066] (Examples 1 to 7, Comparative Examples 1 and 2) First, a "carbon fiber nonwoven fabric" manufactured by Freudenberg Performance Materials was prepared as shown in Table 1. Then, the carbon fiber nonwoven fabric was divided into two types: one that was soaked in a surfactant solution containing a surfactant (Examples 1, 3, 5, and 7), and one that was not soaked in the solution (Comparative Example 1, Examples 2, 4, and 6).

[0067] The surfactant solution was prepared by dissolving a surfactant in pure water, and polyoxyethylene lauryl ether (CAS No. 9002-29-0, manufactured by Nacalai Tesque, Inc.) was used as the surfactant. The concentration was 0.2% by mass. The immersion time was 1 minute. The liquid temperature of the surfactant solution was 40°C.

[0068] Thereafter, those that had been soaked in the surfactant solution (Examples 1, 3, 5, and 7) were dried at 60° C. for 1 hour.

[0069] In Examples 2, 4, and 6, the carbon fibers of the nonwoven fabric were treated with a water-repellent resin to make them water-repellent. That is, a carbon-based nonwoven fabric for cesium adsorption (cesium adsorbent) was obtained by preparing a carbon fiber nonwoven fabric and treating the carbon fibers of the nonwoven fabric with a water-repellent resin to make them water-repellent.

[0070] Comparative Example 2 A commercially available cellulose membrane (manufactured by Advantec Toyo Co., Ltd.), which is a filter paper made of cellulose, was used. Using this cellulose membrane, the same tests as in Example 1 were carried out. Note that the cellulose membrane has no cation adsorption ability and diffusion within the membrane is free, so the membrane potential is almost zero.

[0071] [Table 1]

[0072] In Table 1, "Freudenberg, H23" is a nonwoven fabric made of carbon fiber only (i.e., no water-repellent treatment, coating treatment, etc.). "Freudenberg, H23I2" is a nonwoven fabric made of carbon fiber with a water-repellent treatment using polytetrafluoroethylene (PTFE). "Freudenberg, H24C3" and "Freudenberg, H23C9" are nonwoven fabrics made of carbon fiber that has been treated with a water-repellent treatment using PTFE and further treated with an MPL coating using a coating liquid containing carbon black and PTFE. In particular, the difference between H24C3 and H23C9 is mainly the type of carbon used in the MPL coating treatment; H24C3 uses both carbon black and graphite (type 1), while H23C9 uses carbon black (type 2).

[0073] (1) Measurement of membrane potential: Regarding the cesium ion adsorption of the nonwoven fabric and cellulose membrane, the membrane potential was measured electrochemically using a concentration system in which the same electrolyte was placed in different concentrations in both aqueous solution phases through the membrane (see Figure 2). The membrane potential was measured for three types of salts, CsCl, NaCl, and MgCl2, using a measuring device with a measuring cell (see Figure 1) (see Tables 2 to 4). Note that measurements were made for NaCl and MgCl2 for comparison.

[0074] The measurement device shown in Figure 1 has two spaces separated by a nonwoven fabric or cellulose membrane as a filter, and each space is filled with the same electrolyte solution of different concentrations. During the measurement of the membrane potential, each solution phase is stirred at 90 rpm using a stirrer. The membrane potential was measured using a reference electrode connected to a high input impedance voltmeter. Figure 1 shows a perspective view of the inside of the measurement device.

[0075] More specifically, the membrane potential was measured by creating two aqueous solution phases (first phase 21, second phase 22) via a test subject nonwoven fabric or cellulose membrane (filter) 10 as shown in Fig. 2, and varying the salt concentration of the first phase 21 in the range from 0.001 M to 0.1 M, while fixing the salt concentration of the second phase 22 at 0.1 M. At this time, the potential difference of the first phase 21 with respect to the second phase 22 was taken as the membrane potential.

[0076] The membrane potential was measured by stirring each aqueous solution phase (phase 1 21, phase 22) and connecting the salt bridge to the reference electrode after the entire system had reached a steady state. The membrane potential was then measured using a DUAL DISPLAY MULTIMETER (DL-2051; KENWOOD).

[0077] All membrane potential measurements were performed in a thermostatic reflux device at 25° C. Reagents were from Wako Pure Chemical Industries, Ltd. and used without further purification, and pure water with a resistance of 18 MΩ or higher was used.

[0078] Here, if the membrane (filter) has a high cation adsorption capacity, it will have a fixed charge on the membrane surface, and as a result, the membrane potential will be large, and this property can be used to measure the cation adsorption capacity. Since cellulose membranes have no cation adsorption capacity and ions diffuse freely within the membrane, the membrane potential is nearly 0, so the auto-zero function of the measuring device was used to correct the membrane potential of the cellulose membrane to 0 before measurement.

[0079] Next, the test results for the adsorption of cesium ions are shown in Table 2. The results are explained below.

[0080] Comparing Comparative Example 1 and Comparative Example 2, it is found that the nonwoven fabric made of carbon fibers has a membrane potential of 1.19 and has a higher adsorption capacity for Cs than the cellulose membrane (membrane potential is 0).

[0081] Comparing Example 1 and Comparative Example 1, it can be seen that the nonwoven fabric made only of carbon fibers (Comparative Example 1) has a larger membrane potential and improved Cs adsorption capacity by being treated with a surfactant (Example 1).

[0082] Comparing Examples 2 and 3 with Comparative Example 1, it is clear that the Cs adsorption ability is further improved by subjecting the nonwoven fabric made of carbon fiber (Comparative Example 1) to a water repellent treatment with PTFE (Examples 2 and 3).

[0083] From Examples 4 to 7, it can be seen that when a carbon fiber nonwoven fabric is subjected to a water repellent treatment with PTFE and then further subjected to an MPL coating treatment consisting of carbon black and PTFE, an even higher Cs adsorption ability can be obtained.

[0084] In particular, from Examples 5 and 7, it can be seen that further surfactant treatment results in better cation adsorption ability.

[0085] In terms of the magnitude of the membrane potential, it is believed that the carbon fiber nonwoven fabrics produced in Examples 1 to 7 have a stronger cation adsorption capacity in the order of Cs>Na>Mg (see Tables 2 to 4).

[0086] [Table 2]

[0087] In Table 2, the numbers indicate the membrane potential. The more positive (larger) the membrane potential value, the better the performance.

[0088] In Table 2, "water-repellent treatment" indicates that the carbon fibers of the nonwoven fabric made of carbon fibers are treated to be water-repellent with polytetrafluoroethylene (PTFE). "Water-repellent treatment + MPL coating (type 1)" and "water-repellent treatment + MPL coating (type 2)" indicate that the carbon fibers of the nonwoven fabric made of carbon fibers are treated to be water-repellent with PTFE and further treated with MPL coating using a coating liquid containing carbon black and PTFE. "Surfactant treatment" indicates that a surfactant solution using polyoxyethylene lauryl ether (CAS No. 9002-29-0, manufactured by Nacalai Tesque) as the surfactant is used, as shown in Example 1, and the nonwoven fabric is immersed in this surfactant solution and dried (surfactant treatment).

[0089] In Tables 2 to 4, if the membrane potential is 2.0 or more and less than 4.3, it is indicated as "+". If the membrane potential is 4.3 or more and less than 6.6, it is indicated as "++". If the membrane potential is 6.6 or more and less than 9.0, it is indicated as "+++".

[0090] [Table 3]

[0091] [Table 4]

[0092] (2) Ion specificity of surfactant: Na + ,Cs + ,Ca 2+ ,Mg 2+ The critical micelle concentration (CMC) of a surfactant (polyoxyethylene lauryl ether) was measured in an aqueous solution containing either the cations NaCl, CsCl, or CaCl. 2、The critical micelle concentration of each surfactant (polyoxyethylene lauryl ether) was measured in the presence of 0.1M MgCl2. The Wilhelmy method was used for the surface tension experiment. This is a widely used method for measuring surface tension and has been used for a long time.

[0093] Specifically, a platinum plate was immersed in each aqueous solution, and the force generated by each aqueous solution in the direction of pulling the platinum plate was measured with a balance to calculate the surface tension. The actual measurements were performed using a surface tensiometer "One Attension (Biolin Scientific)" and an automatic titrator "TITRONIC (Biolin Scientific)."

[0094] When ions are present in an aqueous solution, the cations are absorbed by the surfactant, which causes the surfactant to lose water molecules due to hydration, decreasing the surfactant's hydrophilicity and decreasing the critical micelle concentration (CMC). This effect is more pronounced as the valence of the ion increases, since the electrical interaction with the water molecules increases.

[0095] As a result of the measurement, as shown in Figure 3, Cs + is a divalent Mg 2+ The critical micelle concentration of polyoxyethylene lauryl ether is as low as that of Cs + It showed a specific high affinity for ions.

[0096] (3) Adsorption to nonwoven fabric: Mass spectrometry was performed to confirm the adsorption of the surfactant onto the nonwoven fabric. The results are shown in Figure 4(a) to (d).

[0097] In the mass spectrometry (TOF-MS) results shown in Figure 4, compared to the second from the top, "(b) Untreated carbon-based nonwoven fabric," spectra with a constant m / z interval were detected in the nonwoven fabrics treated with surfactants ((a), (c), and (d)). The interval between each spectral peak was approximately 44 Da.

[0098] This interval corresponds to the ethylene oxide (EO, -CH2CH2O-) of the treated surfactant, and this result indicates that the surfactant is water-soluble but is adsorbed to the nonwoven fabric even when placed in the aqueous phase without falling off.

[0099] In FIG. 4, "(a) Surfactant (polyoxyethylene lauryl ether)" is the result of mass spectrometry of only the surfactant polyoxyethylene lauryl ether. In FIG. 4, "(b) Untreated carbon-based nonwoven fabric" is the result of mass spectrometry of only the carbon fiber nonwoven fabric (without surfactant treatment, water-repellent treatment, etc.). In FIG. 4, "(c) Carbon-based nonwoven fabric treated with surfactant concentration of 2.0 wt %" is the result of mass spectrometry of the carbon fiber nonwoven fabric ((b) untreated carbon-based nonwoven fabric) after treatment with a surfactant solution containing 2.0 mass % surfactant (polyoxyethylene lauryl ether) (but without further treatment such as water-repellent treatment). In FIG. 4, "(d) Carbon-based nonwoven fabric treated with a surfactant concentration of 0.20 wt %" is the result of mass spectrometry of a carbon fiber nonwoven fabric ((b) untreated carbon-based nonwoven fabric) after treatment with a surfactant solution containing 0.20 mass % of a surfactant (polyoxyethylene lauryl ether) (but without further treatment such as water repellent treatment).

[0100] Although not shown, judging from scanning electron microscope (SEM) images, it was confirmed that the physical structure of the carbon fibers in the nonwoven fabric treated with the surfactant did not change.

[0101] As can be seen from the above, the carbon fiber nonwoven fabrics of Examples 1 to 7 can be used as filters that adsorb cesium, compared to the nonwoven fabric of Comparative Example 1 and the cellulose membrane of Comparative Example 2. That is, it can be seen that the use of the carbon fiber nonwoven fabrics of Examples 1 to 7 makes it possible to recover radioactive cesium from the environment. In addition, since the nonwoven fabrics of Examples 1 to 7 are made of carbon fiber, they can be easily disposed of. [Industrial Applicability]

[0102] According to the method for producing a carbon-based nonwoven fabric for cesium adsorption of the present invention, a carbon-based nonwoven fabric that can be used as a filter for adsorbing cesium can be produced. Also, the cesium adsorbent of the present invention can be used as a filter for adsorbing cesium. [Explanation of symbols]

[0103] 10: Nonwoven fabric or cellulose membrane (filter) 21: Phase 1 22: Phase 2

Claims

1. A method for producing a carbon-based nonwoven fabric for cesium adsorption, comprising the steps of: immersing a carbon fiber nonwoven fabric in a surfactant solution containing a surfactant; and then drying the fabric to obtain a carbon-based nonwoven fabric for cesium adsorption, The method for producing a carbon-based nonwoven fabric for cesium adsorption uses, as the nonwoven fabric, the carbon fiber that has been subjected to a water-repellent treatment with the first water-repellent resin and then coated with a coating agent containing a second water-repellent resin and a conductive material.

2. 2. The method for producing a carbon-based nonwoven fabric for adsorbing cesium according to claim 1, wherein the surfactant contained in the surfactant solution is polyoxyalkylene lauryl ether.

3. 3. The method for producing a carbon-based nonwoven fabric for adsorbing cesium according to claim 1, wherein the concentration of the surfactant contained in the surfactant solution is 0.05 to 10 mass %.

4. the first water-repellent resin and the second water-repellent resin are each a fluororesin, The method for producing a carbon-based nonwoven fabric for cesium adsorption according to claim 1, wherein the conductive material is carbon black.

5. A method for producing a carbon-based nonwoven fabric for cesium adsorption, comprising the steps of: preparing a carbon fiber nonwoven fabric; and subjecting the carbon fibers of the nonwoven fabric to a water-repellent treatment using a first water-repellent resin to obtain a carbon-based nonwoven fabric for cesium adsorption, The method for producing a carbon-based nonwoven fabric for cesium adsorption includes using the nonwoven fabric that has been subjected to the water-repellent treatment and then coated with a coating agent containing a second water-repellent resin and a conductive material.

Citation Information

Patent Citations

  • Water-added oil

    JP2009292987A

  • Cesium adsorbent

    JP2014108379A

  • Drainage treatment unit and treatment method

    JP2016019933A

  • Volume-reducible radioactive material adsorbent, production method, processing method and adsorption method

    JP2016035435A

  • Flask release agent

    JP2018130957A